Deciphering the Promising Varieties of Pigeon Pea for Wilt Resistance and Yield Potential in the Northern Dry Zone of Karnataka (Journal of Plant Disease Sciences, 2025)
Pigeon pea (Cajanus cajan (L.) Millsp.) is a major legume crop cultivated extensively in rainfed semi-arid regions and plays a vital role in India's pulse production. However, Fusarium wilt (Fusarium udum) is a major constraint, causing significant yield losses.This study aimed to assess the performance of different pigeon pea varieties for wilt resistance and yield potential through on-farm demonstrations in Vijayapur district, Karnataka, over two cropping seasons (2019–20 and 2020–21).
Keywords: Pigeon pea; Fusarium wilt; Yield; Economics